IN THE DEANS’ SHOES: A QUALITATIVE EXAMINATION OF ISSUES REQUIRING STRATEGIC DECISION-MAKING IN TEACHER EDUCATION INSTITUTIONS - Jefferson E Flores (Tạp chí Khoa học Đại học Đà Lạt, 2024)
This qualitative study explores the decision-making processes of deans in teacher education in the Philippines and investigates the challenges they encounter. The research employs a descriptive qualitative approach grounded in the interpretive paradigm, focusing on the experiences and perspectives of current and former deans. Data were collected through interviews, focus group discussions, and reflective essays, with thematic analysis used for data interpretation. Findings reveal key issues necessitating strategic decisions, including performance in licensure exams, introduction of new programs, accreditation demands, inherent functions, and faculty development programs. The identified key issues impact institutional quality, accreditation, and faculty competence. This study underscores the significance of strategic decision-making in teacher education leadership and administration, offering insights for educational policymakers, administrators, and stakeholders. By shedding light on these aspects, this study contributes to continuous improvement in teacher education and the broader educational landscape, aligning with evolving societal needs.